The fundamentals of corrosion and scaling for petroleum and environmental engineers - Chilingar, George V., 1929- (Gulf Pub., 2008)
Scale, or deposits, can build up in the wellbore tubulars and other downhole components, causing considerable damage to the life of the well. Infrastructure provides the support for the wells system and with oil and gas consumption on the rise and transportation required to feed that demand, all petroleum and pipeline engineers must have accurate corrosion and scaling information. The Fundamentals of Corrosion and Scaling for Petroleum and Environmental Engineers will provide the quick knowledge that engineers need to not only enhance the reliability of corrosion and scale control technologies but also manage scale deposits, prevent fatigue and ensure equipment integrity.
Keywords: Oil fields -- Equipment and supplies -- Corrosion.; Corrosion and anti-corrosives.; elektronické knihy; electronic books